Recombinant protein expression in Komagataella pastoris and the scheduling of a multistage, multiproduct facility producing alternative sweeteners from A-molasses - Mamba, Phelelani Eshmael (Stellenbosch : Stellenbosch University, 2025)
Mamba, P. E. 2025. Recombinant protein expression in Komagataella pastoris and the scheduling of a multistage, multiproduct facility producing alternative sweeteners from A-molasses. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/111d8af1-ea00-44b1-add4-d5ea3af09b44